Who moved my interest rate? : leading the Reserve Bank of India through five turbulent years - Subbarao, Duvvuri (Gurgaon Penguin Books, 2016)
This book is a ringside view of running an emerging-market central bank during the financial crisis.
Keywords: Reserve Bank of India - Biography; IAS as an author